2006
DOI: 10.1002/ijc.21801
|View full text |Cite
|
Sign up to set email alerts
|

Air pollution and risk of lung cancer in a prospective study in Europe

Abstract: To estimate the relationship between air pollution and lung cancer, a nested case-control study was set up within EPIC (European Prospective Investigation on Cancer and Nutrition). Cases had newly diagnosed lung cancer, accrued after a median follow-up of 7 years among the EPIC exsmokers (since at least 10 years) and never smokers. Three controls per case were matched. Matching criteria were gender, age (65 years), smoking status, country of recruitment and time elapsed between recruitment and diagnosis.We stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
105
1
4

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(116 citation statements)
references
References 15 publications
6
105
1
4
Order By: Relevance
“…Nafstad et al (2003) examined lung cancer incidence in a cohort of Oslo men and found that it was significantly associated with NO 2 but not SO 2 at the home address estimated using dispersion models. In an international case control study, Vineis et al (2006) found a nonsignificant association with NO 2 concentrations obtained from background monitoring stations. Effect estimates in these three studies were highly comparable at 1.10 (0.97-1.23) in the Swedish study, 1.14 (0.78-1.67) in the international study, and 1.08 (1.02-1.15) in the Norwegian study respectively, for a 10 mg/m 3 increase in NO 2 and NO x , respectively.…”
Section: Mortalitymentioning
confidence: 86%
See 1 more Smart Citation
“…Nafstad et al (2003) examined lung cancer incidence in a cohort of Oslo men and found that it was significantly associated with NO 2 but not SO 2 at the home address estimated using dispersion models. In an international case control study, Vineis et al (2006) found a nonsignificant association with NO 2 concentrations obtained from background monitoring stations. Effect estimates in these three studies were highly comparable at 1.10 (0.97-1.23) in the Swedish study, 1.14 (0.78-1.67) in the international study, and 1.08 (1.02-1.15) in the Norwegian study respectively, for a 10 mg/m 3 increase in NO 2 and NO x , respectively.…”
Section: Mortalitymentioning
confidence: 86%
“…Some characteristics of these five cohort studies are given in Table 1. In addition, studies have examined specifically a relationship with lung cancer (Nyberg et al, 2000;Nafstad et al, 2003;Edwards et al, 2006;Vineis et al, 2006).…”
Section: Mortalitymentioning
confidence: 99%
“…1998; Pope et al, 2002;Vineis et al, 2006), mortality, and lower life expectancy (Chen et al, 2013;Correia et al, 2013;Dockery et al, 1993;Franklin et al, 2007;Goldgewicht, 2007;Laden et al, 2000;Ostro et al, 2006;Pope et al, 2009). Recently a few studies have investigated the associations between particle composition and health effects (Bell et al, 2010(Bell et al, , 2007Burnett et al, 2000;Cao et al, 2012;Franklin et al, 2008;Ito et al, 2011;Krall et al, 2013;Levy et al, 2012;Mar et al, 2000;Ostro et al, 2007Ostro et al, , 2010Son et al, 2012).…”
mentioning
confidence: 99%
“…However, cases of increased respiratory conditions, throat pain, phlegm, acute symptoms like coughing, wheezing, chronic bronchitis emphysema, asthma, chronic obstructive pulmonary disease, chronic rhinitis, chronic pharyngitis have been reported where there is continous exposure to ozone emission (Jones et al 2006). Reduced lung function, higher cardiovascular diseases and stroke mortality have been associated with ambient ozone levels (Finkelstein et al, 2005;(Vineis et al, 2006).…”
Section: Effects Of Ozone Emissions On Human Healthmentioning
confidence: 99%